(untitled) (Research, Society and Development, 2020)
Chemistry as Science has been conceived and established throughout its development based on social and historical concerns and it is essential to recognize this in order to overcome the ready and finished perception of Science. The main question in this research is to identify how the Chemistry teacher training courses present the History of Chemistry as a subject in their curriculum? Our general objective was to verify the presence of the subject History of Chemistry in the early training of Chemistry teachers, through the analysis of its organization in the PPPs of the Chemistry Graduation Courses in Public Universities of the State of Ceará. The research had a qualitative preference, with the Documental Research being used as a method. The PPPs analyzed, as a reference for the teaching profession, need to be reconsidered with regards to the presence of the History of Chemistry subject, which has to be integrated with the skills and abilities required from the undergraduate student, its compulsory nature, content and course duration, in order to provide reliable training in the History of Chemistry in the undergraduate student’s curriculum. It is imperative to provide a means of overcoming the discrepancies identified in several PPPs analyzed, how to make the History of Chemistry curricular component mandatory during the course, with the premise of a work focused on the historiography of Chemistry, since training critical and reflexive teachers requires a teacher with the same attributes, in addition to confidence and pedagogical accuracy, enabling future chemistry teachers to be able to incorporate the didactic transposition of knowledge into their teaching in High School.